Pengungkapan Environmental, Social and Governance (ESG) pada Pemerintah Daerah: Analisis Bibliometrik - Yesica Arinda Damayanti; Indrawati Yuhertiana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Environmental, Social and Governance (ESG) disclosure in local governments is needed to increase the disclosure of non-financial information to the public and stakeholders. The aim of this research is to analyze the development of research regarding ESG disclosure in local governments. The research method used is bibliometric analysis which maps deep research database Google Scholar from 2019-2023. After going through the filtering process, 57 articles were obtained which were processed using the application Publish or Perish and VOSviewer. The research results show that there are 6 clusters that explain the aspects and factors that are interrelated in the formation of ESG disclosures in local governments. The research results also show that ESG disclosure in local governments is still a hot topic for research. It is hoped that this research can contribute to future researchers and add information related to ESG disclosure to local governments.